2018
DOI: 10.1098/rstb.2017.0175
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble allosteric model: energetic frustration within the intrinsically disordered glucocorticoid receptor

Abstract: Allostery is an important regulatory phenomenon enabling precise control of biological function. Initial understanding of allostery was gained from seminal work on conformational changes exhibited by structured proteins. Within the last decade, protein allostery has also been demonstrated to occur within intrinsically disordered proteins. This emerging concept of disorder-mediated allostery can be usefully understood in the context of a thermodynamic ensemble. The advantage of this ensemble allosteric model is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 75 publications
1
35
0
Order By: Relevance
“…The picture that has emerged from various domains of biology is that allostery involves the interplay of a spectrum of dynamically linked states [ 11 17 ]. In some systems, it is straightforward to partition these states into the physiologically relevant categories; for example, CRP naturally divides into the cAMP unbound, singly bound, and doubly bound states as well as the DNA bound and unbound states.…”
Section: Introductionmentioning
confidence: 99%
“…The picture that has emerged from various domains of biology is that allostery involves the interplay of a spectrum of dynamically linked states [ 11 17 ]. In some systems, it is straightforward to partition these states into the physiologically relevant categories; for example, CRP naturally divides into the cAMP unbound, singly bound, and doubly bound states as well as the DNA bound and unbound states.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, thermodynamic analysis of the stability and DNA binding affinities of various isoforms of GR (13), revealed that the GR A isoform exists in a frustrated state, wherein the Rdomain ( Fig. 6A) decreases the probability of the GR A being in its active conformation (29). This occurs because the R-domain is both positively coupled and, therefore, stabilized by the DBD, and also negatively coupled, therefore destabilizing, to the F-domain, which is responsible for interaction with TSG101cc.…”
Section: The Effect Of Energetic Frustration On Tsg101:gr a Bindingmentioning
confidence: 99%
“…A more recent model of the allosteric process is named EAM (ensemble allostery model) (Hilser et al, 2012;Tsai and Nussinov, 2014;Choi et al, 2015;White et al, 2018). It provides a generalization of both MWC and KNF models, allowing the treatment of a set of different populated conformational states (Hilser et al, 2012).…”
Section: Models Of Allosteric Phenomenonmentioning
confidence: 99%